The Impact of a National Stewardship Policy on the Usage Patterns of Key Monitoring Drugs in a Tertiary Teaching Hospital: An Interrupted Time Series Analysis - Haiyan Li; David J. McIver; Wenjing Ji; Jiaxi Du; Hang Zhao; Xiaoni Jia; Xiaoni Jia; Yuyao Zhai; Xiaorong Xue (Frontiers Media S.A., 2022)
Background: The management of Key Monitoring Drugs has become one of important aspects to control the growth of pharmaceutical expenditures in China. The first batch of the China National Key Monitoring Drugs (NKMDs) policy was released in July 2019. However, little is known about the impact of the national stewardship on the trends of NKMDs prescribing practice in hospitals, especially in the Northwestern China.Methods: We collected 8-years of monthly NKMDs usage data from a tertiary hospital between 2014 and 2021. A segmented regression model of interrupted time series (ITS) analysis was used to evaluate the Defined Daily Doses (DDDs) and spending trends of ten NMKDs in the hospital throughout the study period. The pre-implementation period was from January 2014 to November 2019 and the post-implementation period was from December 2019 to June 2021.Results: Prior to the implementation of the NKMDs policy, there was an increasing trend both in DDDs and spending for 8 of 10 NKMDs. The interventions managed by clinical pharmacists after the implementation of the national stewardship policy led to a significant decreasing trend of DDDs in the 19 months following implementation, of 430 fewer DDDs per month in total, compared to the pre-implementation period (p < 0.001). A similar decrease in spending was seen in the post-implementation period, with a trend of $4,682 less total spending on medications in those months compared to the pre-implementation trend (p = 0.003). There was a significant decrease in both monthly DDDs and spending for 6 of the 10 medications in the post-implementation period, while there was a significant increased trend both in monthly DDDs and spending on 1 medication in that period.Conclusion: Using ITS analysis, the total DDDs and spending on 10 NKMDs in this hospital indicated sustained reductions over 19 months after multidimensional interventions under the implementation of the national policy guidance. The national stewardship policy could therefore be considered an effective strategy. Additional comprehensive policies should be introduced to further improve the rational use of NKMDs.